Caracterización clínica de la osteopenia del recién nacido pretérmino - Cava Guanga, Jessica Alejandra (2023)
ABSTRACT: Introduction: Osteopenia of prematurity is a multifactorial systemic disease. The premature infant is deprived of the accumulation of calcium and phosphorus in the uterus that occurs during the third trimester of pregnancy. It occurs between 4 and 6 weeks of life. The clinical manifestations are diverse according to the degree of demineralization. Prevention is more important than treatment, it consists of avoiding risk factors, optimizing newborn nutrition and physiotherapy. Objective: To carry out a bibliographic review to obtain detailed information on the clinical characterization of osteopenia in the preterm newborn. Methodology: A bibliographic review was carried out by recovering 76 articles from international journals in databases such as Scielo, Redalyc, Latindex, Scopus, Pubmed, Cochcrane, Medline. Results: The clinical characterization of osteopenia in the preterm newborn indicates that the clinical manifestations begin from 5-12 weeks of age, and in turn may have a second time of presentation from 18 months to 12 years of age. However, most of them present asymptomatically. The risk factors that contribute to the development of osteopenia in premature infants are gynecological and obstetric risk factors such as deficient maternal reserves of calcium, phosphorus and vitamin D, certain conditions such as preeclampsia, intrauterine growth restriction, chorioamnionitis and preterm labor. Neonatal risk factors are prematurity and low birth weight. Risk factors related to health care are the use of certain medications such as corticosteroids and loop diuretics, prolonged parenteral nutrition, and feeding with unfortified breast milk. Comorbidities that predispose to the development of osteopenia are chronic lung disease, chronic pulmonary dysplasia, necrotizing enterocolitis, neonatal cholestasis, cholestatic jaundice, and sepsis. Conclusion: Knowledge related to the etiopathogenesis, risk factors, comorbidities, diagnostic criteria, treatment and complications of osteopenia in premature infants were updated, since this is a key point to reach early diagnosis and early treatment of this condition.